N-glycosylation of TREK-1/hK2P2.1: two-pore-domain potassium (K2P) channels - Wiedmann, Felix Tobias; Kraft, Manuel; Ratte, Antonius; Thomas, Dierk; Katus, Hugo; Schmidt, Constanze (International journal of molecular sciences, 2019)
Mechanosensitive hTREK-1 two-pore-domain potassium (hK2P2.1) channels give rise to background currents that control cellular excitability. Recently, TREK-1 currents have been linked to the regulation of cardiac rhythm as well as to hypertrophy and fibrosis. Even though the pharmacological and biophysical characteristics of hTREK-1 channels have been widely studied, relatively little is known about their posttranslational modifications. This study aimed to evaluate whether hTREK-1 channels are N-glycosylated and whether glycosylation may affect channel functionality. Following pharmacological inhibition of N-glycosylation, enzymatic digestion or mutagenesis, immunoblots of Xenopus laevis oocytes and HEK-293T cell lysates were used to assess electrophoretic mobility. Two-electrode voltage clamp measurements were employed to study channel function. TREK-1 channel subunits undergo N-glycosylation at asparagine residues 110 and 134. The presence of sugar moieties at these two sites increases channel function. Detection of glycosylation-deficient mutant channels in surface fractions and recordings of macroscopic potassium currents mediated by these subunits demonstrated that nonglycosylated hTREK-1 channel subunits are able to reach the cell surface in general but with seemingly reduced efficiency compared to glycosylated subunits. These findings extend our understanding of the regulation of hTREK-1 currents by posttranslational modifications and provide novel insights into how altered ion channel glycosylation may promote arrhythmogenesis.
Im Titel ist 2P tiefgestellt
Gesehen am 31.01.2020